Relationships between climate change, human environmental impact, and megafaunal extinction inferred from a 4000-year multi-proxy record from a stalagmite from northwestern Madagascar. (15th April 2020) - Railsback, L. Bruce; Dupont, Laura A.; Liang, Fuyuan; Brook, George A.; Burney, David A.; Cheng, Hai; Edwards, R. Lawrence
Abstract: Stalagmite ANJ94-2 from Anjohibe Cave in northwestern Madagascar provides an exceptionally detailed and precisely dated record of changing environmental conditions that, combined with previously published data from stalagmites, wetland deposits, and archaeological sites, allows insights into past climate change, human environmental impact, and megafaunal extinction. Proxies of past conditions recovered from Stalagmite ANJ94-2 include ratios of carbon and oxygen stable isotopes (δ 13 C and δ 18 O), mineralogy (calcite and aragonite), layer-bounding surfaces, layer-specific width, and detrital material. Those proxies suggest that the natural environment changed in response to changes in rainfall at time scales of a few decades to multiple centuries; comparison with distant proxies suggests that wetter conditions in northwestern Madagascar may have been linked to cooling in the Northern Hemisphere. Carbon isotope data nonetheless suggest that the greatest environmental change in the area coincided with human introduction of swidden ( tavy ) agriculture about 1200 years ago, during a time not of drought but perhaps of slightly increasing wetness. The timing and extent of environmental change 1200 to 600 years ago seen in stalagmite and wetland data suggest that human modification of the landscape had a causal role in the extinction of Madagascar's megafauna. On the other hand, the results combine with other recent research to indicate that drought was not the cause of the megafaunal extinction. Highlights: Long and continuous stalagmite record of climate and human influence in Madagascar. Undisturbed natural environmental until 700–800 CE, with 800-year climate cycles. Major disruption of vegetation and soil ecosystem began in 700–800 CE. Disruption coincides with increase of evidence of human activity in the region. Drought was not responsible for environmental change and extinction.